Autonomy and control : the collapse of Royal Imtech - Yue, Tao, active 2017; Beuken, Melanie; Roelofsen, Erik (London : Rotterdam School of Management, Erasmus University, 2017)
In 2012, the Dutch construction company Royal Imtech was the stock markets' darling. Its results were rocksteady and the company recorded consistent growth, mainly through acquisitions. The CEO and CFO formed a close duo that kept repeating their mantra: the secret to the success of Royal Imtech was local entrepreneurship. However, underneath the bright surface was a company that was on the edge of its collapse. The dogmatic approach to entrepreneurship and autonomy resulted in a leadership team that was out of control. Local managers bamboozled leadership, making them believe in fabricated profits. The German CEO engaged in collusion, outright fraud, and corruption in order to maintain the success story. With projects that had become larger and larger, losses could no longer be swept under the rug. When an analyst noticed that the numbers of Royal Imtech smelled fishy, he ushered Royal Imtech into its eventual bankruptcy.
Originally Published In : Yue, T., Beuken, M., & Roelofsen, E. (2017). Autonomy and Control: The Collapse of Royal Imtech. Rotterdam, Netherlands: Rotterdam School of Management, Erasmus University.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Corporations -- Corrupt practices -- Case studies